2016
DOI: 10.1007/978-3-319-42023-3_1
|View full text |Cite
|
Sign up to set email alerts
|

Image Analysis of the Tumor Microenvironment

Abstract: In the field of pathology it is clear that molecular genomics and digital imaging represent two promising future directions, and both are as relevant to the tumor microenvironment as they are to the tumor itself (Beck AH et al. Sci Transl Med 3(108):108ra113-08ra113, 2011). Digital imaging, or whole slide imaging (WSI), of glass histology slides facilitates a number of value-added competencies which were not previously possible with the traditional analog review of these slides under a microscope by a patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Current advances include protocols to reconstruct the spatial 3D architectures of DCIS from 2D histology images stained with haematoxylin and eosin (H&E) [139] and multi-tiered content-based image algorithms for classification of tumour grades [140]. Histology samples and digital microscopy analyses were also used to evaluate the differences between distinct regions of interest within the same tumour [141]. Such approaches allow for the assessment of tumour phenotypic features and tumour microenvironment landscapes at different levels of resolution [142].…”
Section: Medical Imagingmentioning
confidence: 99%
“…Current advances include protocols to reconstruct the spatial 3D architectures of DCIS from 2D histology images stained with haematoxylin and eosin (H&E) [139] and multi-tiered content-based image algorithms for classification of tumour grades [140]. Histology samples and digital microscopy analyses were also used to evaluate the differences between distinct regions of interest within the same tumour [141]. Such approaches allow for the assessment of tumour phenotypic features and tumour microenvironment landscapes at different levels of resolution [142].…”
Section: Medical Imagingmentioning
confidence: 99%
“…Malignant tumors (Tridosaja) are very harmful, because they can affect all three major body systems, i.e. the nervous system (Vata or air), the venous system (Pitta or fire), and the arterial system (Kapha or water) lose mutual coordination and thus cannot prevent tissue damage, resulting in a deadly morbid condition [12,13]. In modern medical point of view, the cancer is defined as abnormal cell division due to a number of conditions.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Breast cancer is the common problem of not only in developed nations but also in developing countries [11]. It has been found that breast cancer is common to a large part of women [12]. In India, the death toll due to breast cancer is increasing at a rapid pace [13].…”
Section: Literature Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…This combination meets the standards of high definition, high speed, and high throughput screening [11], which could lay a good foundation for the development and application of digital pathology. Using whole slide imaging (WSI) as the basis, combined with a series of technical equipment including (i) a image analysis system and (ii) an information management system, via deep learning of the computer, AI can effectively simulate a pathologist's brain for effective thinking and further assist in broader applications in the medical and health areas, such as disease intelligence analysis, tumour-assisted diagnosis, gene data detection, and disease drug development [12][13][14][15]. Generally, WSIs are gigapixel images stored in a multi-resolution pyramid structure where the highest resolution is × 40.…”
Section: Introductionmentioning
confidence: 99%